KEANEKARAGAMAN TUMBUHAN DAN POTENSINYA DI CAGAR ALAM TANGALE, GORONTALO - Rugayah, Rugayah; Sunarti, Siti; Djarwaningsih, Tutie (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Plant inventory has been carried out in Tangale Nature Reserves in GorontaloProvince, North Sulawesi (2002). This area covers about 113 ha. About 250species have been listed from this area, and 72 species of them utilized by thelocal people who leave in its surrounding area as stuff food, fruit and vegetablesources, medicinal purpose, ornamental plant and for house building as well. Fromthis activity, one new species of Oxalidaceae (Averrhoa leucopetala Rugayah &Sunarti) described, and two species of Euphorbiaceae (Mallotus griffithianus andM. macrostachys) informed as a new record for Sulawesi.